Inventory, colony fluctuation, and wasp nesting social habits in IFSULDEMINAS - Machado Campus - Fortes, Elenice Aparecida; Fortes, Alice dos Reis; de Almeida, Letícia Cruz; Fernandes, Lêda Gonçalves (Revista Agrogeoambiental, 2021)
Social wasps offer important ecosystem resources as biological control and pollination. Many species are synanthropic, however, there are still few studies of these insects in anthropized environments. The objective of this study was to verify the richness, colony fluctuation, and preferential substrates for social wasp nesting at IFSULDEMINAS Campus Machado. Four censuses/inventories were carried out from November 2015 to June 2016, and the active collection method with an entomological net was used for wasp collection. The specimens found were assembled, identified, and deposited in the collection of the entomology laboratory of the institution. In total, 20 species of social wasps were registered, from which the genera Polybia, Polistes, and Mischocyttarus showed a greater richness of species. The number of colonies increased from November to March, decreasing in June. Mischocyttarus cassununga R. von Ihering (1903) had more abundance of colonies in all months evaluated. Broadly, the genera Mischocyttarus and Polistes presented nesting preference for the building substrate, while the genus Polybia presented preference for the vegetation substrate. Machado Campus has a diversity of environments that contributes to the establishment of social wasp colonies. Therefore, it is essential to disseminate this information and environmental education actions to the community to demonstrate the importance of these insects for the ecosystem and the need for environmental conservation to guarantee their ecosystem services.